Time to intravenous antibiotic administration (TIbiA) in severe open tibial fractures: Impact of change to national guidance. Issue 4 (April 2020) - Hendrickson, Susan A.; Donovan, Richard; Harries, Luke; Wright, Thomas C.; Whitehouse, Michael R.; Khan, Umraz
Highlights: National UK guidance recommends intravenous antibiotics within 1 h of injury in severe open tibial fractures. This study found no association between deep infection and time to administration of intravenous antibiotics in such patients. We report a low deep infection rate (7.5%), which may be due to expedient, expert care delivered by a dedicated specialist orthoplastic team. Abstract: Introduction: Severe open tibial fractures are limb-threatening injuries. Outcomes depend on a complex interplay of patient, injury and treatment factors. 2009 guidelines from the British Orthopaedic Association (BOA) and British Association of Plastic, Reconstructive and Aesthetic Surgeons (BAPRAS) recommend prophylactic intravenous antibiotic administration within three hours of injury. More recent National Institute for Health and Care Excellence (NICE) 2016 guidelines recommend pre-hospital antibiotic administration where possible. This study aimed to analyse the impact of time to antibiotics on development of deep infection. Methods: Adult acute Gustilo-Anderson 3B open tibial fractures managed at a single UK Major Trauma Centre were reviewed retrospectively over a three-year period, including a period before and after the regional ambulance service introduced a policy of administering pre-hospital intravenous antibiotics to open fractures in 2016. Development of deep infection was recorded as the primary outcome measure. Complete case regression analysis was performed. Time was assessed as a continuous variable and as thresholds with antibiotics received within one or three hours of injury. Results: 156 patients with 159 fractures were included. Following introduction of new guidance in 2016, median time to antibiotics decreased from 180 to 160 min and more patients received pre-hospital antibiotics (2% vs. 33%). Overall, 7.5% developed deep infection ( n = 12) within a median follow-up of 26 months. Logistic regression found no relationship between any independent variable, including time to antibiotic administration, and development of deep infection. Conclusions: There are a variety of factors identified in the literature and in national policies and treatment guidelines as potentially modifiable to reduce the risk of deep infection following open fractures. In this study, time to antibiotic administration was not associated with the risk of developing deep infection. The results of this study demonstrate a low infection rate, which may be due to expedient expert care delivered by a dedicated orthoplastic service in line with national guidance where achievable.